O processo criativo e a construção da memória em Cyro dos Anjos - Chagas, Angélica Pereira Martins (2023)
Cyro dos Anjos was a writer from Minas Gerais, born in Montes Claros, who, even with few published works, marked his relevance in the context of Brazilian literature. The aim of this study is to analyze issues of autobiography, literature and memory in the works of Cyro dos Anjos, especially with regard to his volume of memoirs: A Menina do sobrado. Antonio Candido states that “Cyro dos Anjos, a subtle artist of memories, builds his work in a confluence of the past with the present” (CANDIDO, 2011, p.82), in this work this confluence is presented, in addition to other aspects analyzed. The first chapter brings a journey through the life and work of the writer in focus and, in addition, the works A criação literária and Poemas Coronários are used to highlight the author's literary path in all its nuances. For the second chapter, it was intended to build an analysis from the work A Menina do sobrado, starting from the concepts of self-writing, using the studies of Roland Barthes, Michel Foucault, Philippe Lejeunne, Leonor Arfuch, Diana Klinger among others; and memory, time and space, according to Henri Bergson, Paul Ricoeur, Maurice Halbwachs, among other authors. In the third chapter, a visit to the Acervo de Escritores Mineiros at UFMG is reported, in which the archive of Cyro dos Anjos could be observed and analyzed and, also, discussions are carried out from the analysis of the letters between Cyro dos Anjos and Carlos Drummond de Andrade, with theoretical support from Reinaldo Marques, Wander Melo Miranda and other scholars. This thesis intends to contribute to the studies about the author montes-clarense, highlighting a little of the writer's trajectory in his literary creation and providing an immersion in his memories from childhood to adulthood.